2021
DOI: 10.1039/d0tc05379a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new phosphorviaaliovalent cation substitution: DFT predictions, phase transition and luminescence properties for lighting and anti-counterfeiting applications

Abstract: Aliovalent substitution induces phase transition, generating new hosts for luminescence applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…XRD was carried out exploiting a PANalytical X'pert Pro MPD diffractometer with Cu-Kα-radiation ( λ = 1.54056 Å). 36 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD was carried out exploiting a PANalytical X'pert Pro MPD diffractometer with Cu-Kα-radiation ( λ = 1.54056 Å). 36 …”
Section: Methodsmentioning
confidence: 99%
“…XRD was carried out exploiting a PANalytical X'pert Pro MPD diffractometer with Cu-Ka-radiation (l ¼ 1.54056 Å). 36 A LabRAM HR Evolution (Horiba) and NOVA (ideaoptics/ ideaoptics.com/, Shanghai, China) spectrometers were employed for Raman spectroscopy in the backscattering conguration with 785 nm and 532 nm excitation by Cobolt 08 NLD (Narrow Linewidth Diode) laser and Nd:YAG, respectively. Both laser modules were Diode-Pumped Solid-State (DPSS).…”
Section: Characterizationmentioning
confidence: 99%
“…Therefore, a hybrid functional PBE0 was applied to obtain the band gap value of 5.90 eV, confirming the experimental value. 3,24 The excitation energy (300–500 nm, 2.48–4.14 eV) was far lower than the band gap value, ruling out the possible origin of the self-trapped exciton. It was reported that the exchange couple pairs of transition metal ions shortened the luminescence decay time.…”
Section: Resultsmentioning
confidence: 95%
“…2 Because of the high visual sensitivity of humans for green light, we developed a green-emitting security ink made of polyvinyl alcohol and Sr 33 Lu 6 (PO 4 ) 28 :Eu 2+ green phosphor. 3 Compared to the single-color emitting phosphor, multi-color phosphors raise the dimension of secrecy level. Blue and red light anti-counterfeiting was achieved in the dynamic multicolor ZnS:KBr:Mn 2+ phosphor under 302 and 365 nm excitation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that CaCd 2 Ga 2 Ge 3 O 12 (CCGGO) garnet structure is a potential host material with high structural stability and excellent optical properties. 24,25 The rare-earth ion, Tb 3+ , is reported to be capable of emitting 540 nm green fluorescence corresponding to the characteristic transition of 5 D 4 -7 F 5 ; Tb 3+ -doped luminescence anti-counterfeiting materials have frequently been reported recently. In addition, Yb 3+ is considered to be an upconversion sensitiser to absorb 980 nm of near-infrared (NIR) radiation to achieve high-energy luminescence.…”
Section: Introductionmentioning
confidence: 99%